Samorząd terytorialny w poglądach Stanisława Podwińskiego - Podkowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article presents the most important scholarly achievements of Stanisław Podwiński and his views on local government. Podwiński was not only a local government theorist but, above all, practitioner. This is evidenced by his work in various government and local government bodies as well as his instructions on how to elect municipal councillors and members of municipal executive boards as well as village, county and city councillors. The instructions were a kind of signposts showing those organising elections how they should proceed. Podwiński’s instructions were written in a manner that would make them useful not only to state and local government officials, professionally involved in the work of local government, but also to local government activists. The personnel of local government bodies included people who were not always familiar with the scope of responsibilities of the work, which was by no means easy. These publications were to help them discharge their official duties by introducing them to the local government system
Keywords: samorząd terytorialny; Podwiński, Stanisław (1898-1964); administracja samorządowa